In Vivo Alterations in Drug Metabolism and Transport Pathways in Patients with Chronic Kidney Diseases. Issue 2 (6th September 2013) - Joy, Melanie S.; Frye, Reginald F.; Nolin, Thomas D.; Roberts, Brittney V.; La, Mary K.; Wang, Jinzhao; Brouwer, Kim L.R.; Dooley, Mary Anne; Falk, Ronald J.
<x xml:space="preserve">Abstract</x> Study Objective This study was designed to prospectively evaluate the in vivo activities of drug transporters, metabolizing enzymes, and pharmacokinetics in patients with chronic kidney diseases (CKD) caused by glomerulonephritis and nonglomerular etiologies. Design A prospective study design. Participants Eighteen adults with CKD. Setting General Clinical Research Center at the University of North Carolina and University of Pittsburgh. Measurement and Main Results Blood and urine were collected and assayed for fexofenadine (transporter function) as well as flurbiprofen and 4‐hydroxyflurbiprofen (CYP2C9 function). CYP3A4 activity was assessed by the erythromycin breath test. In patients with glomerulonephritis, the apparent oral clearance of fexofenadine (representing transporter activity) was 58.8 ± 34.4 L/hour, documenting a 40% reduction compared with previous data in healthy controls. The CYP2C9 pathway (4‐hydroxyflurbiprofen formation clearance) was similar in all the patients with CKD and was concordant with previous reports of patients with end‐stage renal disease (ESRD) and healthy controls. For flurbiprofen, patients with glomerulonephritis had higher oral clearance than those with nonglomerular CKD, suggesting higher unbound fraction and enhanced metabolism through other (non‐CYP2C9) routes. No statistically significant differences in CYP3A4 activity were observed in either group of patients or when compared with results from previous studies of patients with ESRD or healthy controls. Conclusions The current study suggests no statistically significant differences in the in vivo activity of CYP2C9 and CYP3A4 in patients with either glomerulonephritis or nonglomerular CKD. However, there are clinical differences in transporter function as defined by at least a 25% reduction in activity in glomerulonephritis as opposed to healthy controls. A similarity in the in vivo function between patients with glomerulonephritis and ESRD, and between patients with glomerulonephritis and nonglomerular CKD was present despite significant differences in kidney function. Further in vivo and in vitro studies are necessary to fully understand the physiologic and disease‐specific nuances that contribute to alterations in drug disposition in patients with kidney diseases.